The Role of Cytokines in The Pathogenesis of Periodontal Disease - Abdullaeva Nilufar Ikrombekovna (International Journal of Scientific Trends, 2024)
The pathogenesis of periodontitis is complex and involves a combination of innate and acquired immune mechanisms. The immune system responds to the presence of periodontopathic microorganisms by initiating an inflammatory response. This response involves the release of various cytokines and immune cells, which contribute to tissue damage.The inflammatory process in periodontal tissues progresses through different stages, starting with the infiltration of immune cells into the gingival tissues. The immune cells release pro-inflammatory cytokines, such as interleukin-1 (IL-1), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α), which further promote inflammation and tissue destruction.